Real- time control design and simulation with MATLAB-Simulink using TERASOFT Electro-Mechanical Engineering Control system (EMECS) - Chong, Shin Horng (Penerbit UTeM Press, 2021)
This book covers the data acquisition system and real-time application of control theory with MATLAB/Simulink. Content includes simulation and real-time experiments in the topics of open-loop system, closed-loop system, controller design, system identification and fuzzy logic. This book targets the student who is learning a control system engineering course or doing final year project research or postgraduate research. Even an experienced engineer, this practical and hands-on application guided will give you the confidence to troubleshoot a system or set up a new system. This book offers control theory and hands-on laboratories activities that are useful for them to start their control engineering experiences. Through this book, the reader will relate control theory and its applications to industry-relevant systems.